Support for learning under naturalistic conditions - Lucy M. Cronin-Golomb; Patricia J. Bauer (Cognitive Research, 2022)
Abstract Educational opportunities occur through naturalistic everyday life experiences (e.g., reading a newspaper, listening to a podcast, or visiting a museum). Research primarily examines learning under controlled conditions, such as in a classroom or laboratory. There is relatively little known about the extent to which adults extract semantic content, beyond factual recall, from naturalistic educational experiences. In the present work, we focused on virtual museum exhibits. The materials were sourced directly from an art history museum. The naturalistic nature of this work stems from the type of content used though an important component of naturalistic learning—motivational processes—was not measured. In each of three experiments, we assessed adult learners’ performance on tests of factual recall, inferential reasoning, and self-derivation through memory integration from naturalistic virtual museum exhibits. In anticipation of the potential challenge associated with learning outcomes under naturalistic conditions, we administered a yoked protocol under which participants had opportunities to engage in retrieval practice (Experiment 2a) or restudy (Experiment 2b) as explicit mechanisms of support for the three tests of learning. In all experiments, participants performed successfully on all three tests of learning; factual recall was the most accessible of the three learning outcomes. There was no difference in performance at the group level across experiments, but there was at the individual level, such that idea units generated during retrieval practice predicted learning outcomes, whereas restudy of those exact idea units did not. The current work provides novel insight into mechanisms underlying adult learning from naturalistic educational opportunities.